Traveling Dalam Al-Qur’an: Studi Penafsiran Ayat-ayat Riḥlah dan Safar dalam Tafsir Al-Azhar - Najib, Jauhar; Sulthoni, Akhmad; Mukharom Ridho, Muhammad (Journal of Islamic Scriptures in Non-Arabic Societies, 2024)
In this world, living beings, particularly humans, are constantly driven to move and travel, aiming to achieve better outcomes both in this life and the hereafter. This movement can be seen as an effort to meet various human needs, as explained by Abraham Maslow in his hierarchy of needs, which ranges from basic physiological needs to higher levels of self-actualization. People embark on journeys to secure sustenance, fulfill religious duties such as studying, performing Hajj and Umrah, visiting friends to strengthen bonds, assisting those in need, and visiting the sick. These activities not only satisfy physiological and safety needs but also foster social connections, esteem, and ultimately lead to self-actualization. The encouragement from Allah and His Messenger to travel the earth to witness the majesty of Allah's creation aligns with the pursuit of self-actualization as described by Maslow. This study seeks to explore the meanings of Riḥlah and Safar as interpreted in Tafsir Al-Azhar. The research utilizes the tafsir maudhu'i method, with Buya Hamka's Tafsir al-Azhar serving as the primary source, alongside other scholarly works. The methodology involves defining the theme, gathering relevant verses, and analyzing them with a focus on the selected source. The findings indicate that Riḥlah in the Qur'an, as interpreted by Buya Hamka, refers to traveling for trade or business, a common practice among Arabs, including the Prophet. Meanwhile, Safar is understood as a journey, often linked with the relief (rukhshoh) granted to travelers, illustrating how these travels fulfill various human needs as outlined by Maslow.